2016
DOI: 10.3177/jnsv.62.277
|View full text |Cite
|
Sign up to set email alerts
|

Proline Decreases the Suppressive Effect of Histidine on Food Intake and Fat Accumulation

Abstract: SummaryWe recently suggested that proline might decrease the suppressive effect of histidine on food intake. Our purpose in the present study was to investigate the influence of proline on the suppressive effect of histidine on food intake and accumulation of body fat. Male Wistar rats were divided into four groups and allowed free access to the following diets for 3 wk: control (C), 5% proline (P), 5% histidine (H), or 5% histidine plus 10% proline (HP) diets. Food intake for 7 d and retroperitoneal fat tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 20 publications
2
11
0
Order By: Relevance
“…Altered function of the immune system, allergic reactions, and/or peptic ulcers have not been reported after HIS administration. However, HIS administration has been shown to affect brain function [62][63][64][65][66][67][68].…”
Section: Effects Of Dietary His On Histamine Levelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Altered function of the immune system, allergic reactions, and/or peptic ulcers have not been reported after HIS administration. However, HIS administration has been shown to affect brain function [62][63][64][65][66][67][68].…”
Section: Effects Of Dietary His On Histamine Levelsmentioning
confidence: 99%
“…Increased HIS intake in the form of a dried bonito broth has improved mood state and mental task performance of human subjects [33,34,36]. Several studies have reported an anorectic effect of HIS administration [65][66][67][68] and HIS-enriched diet [62][63][64]. Insufficient HIS intake reduces the brain histamine content and is associated with anxiety-like behaviors in mice [61].…”
Section: Effects Of Dietary His On Histamine Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to histamine, histidine can cross the blood brain barrier. After crossing the blood-brain barrier, and once in the tuberomammilary nucleus (TMN) of the hypothalamus, histidine is converted into histamine by histidine decarboxylase [20]. Subsequently, histamine is oxidized to imidazoleacetaldehyde and then to imidazoleacetic acid [11].…”
Section: Physiological Role Of Histidine Is Common For All Speciesmentioning
confidence: 99%
“…Histamine is a neurotransmitter [23] that plays a role in the control of food intake, along with other neurotransmitters (catecholamines, 5-hydroxytryptamine). Studies have shown that histidine decreases food intake through histamine [20,21]. Vaziri et al studied the effect of histidine administered by intragastric or intraperitoneal routes to rats and measured food intake after blocking the conversion of histidine to histamine by FMH, a-fluoromethylhistidine.…”
Section: Physiological Role Of Histidine Is Common For All Speciesmentioning
confidence: 99%